2017
DOI: 10.1186/s12879-017-2392-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower genetic variability of HIV-1 and antiretroviral drug resistance in pregnant women from the state of Pará, Brazil

Abstract: BackgroundThe present study aimed to describe the genetic diversity of HIV-1, as well as the resistance profile of the viruses identified in HIV-1 infected pregnant women under antiretroviral therapy in the state of Pará, Northern Brazil.MethodsBlood samples were collected from 45 HIV-1 infected pregnant to determine the virus subtypes according to the HIV-1 protease (PR) gene and part of the HIV-1 reverse transcriptase (RT) gene by sequencing the nucleotides of these regions. Drug resistance mutations and sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…This was consistent with other data from Brazil [12][13][14][15][16][17][18][19][20] with the exception of the southern states, where subtype C has been found to prevail. 21 To a lesser extent, presence of recombinant forms between subtypes B and F, K and between F and subtype F1 was also found.…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with other data from Brazil [12][13][14][15][16][17][18][19][20] with the exception of the southern states, where subtype C has been found to prevail. 21 To a lesser extent, presence of recombinant forms between subtypes B and F, K and between F and subtype F1 was also found.…”
Section: Discussionsupporting
confidence: 92%
“…In 97 ARV naïve individuals from Amapá state, subtype B represented 74% [24]. Subtype B was also highly prevalent in Pará state representing 97% of 34 protease sequences of pregnant women [25] and 85% in patients failing HAART [22]. A previous study in 31 HIV-1 sequences of blood donors from Amazonas also showed the predominance of subtype B [21] and a recent study in 129 antiretroviral naïve children from Manaus showed 80.2% subtype B infections [27].…”
Section: Discussionmentioning
confidence: 99%
“…Different rates of TDR to the main ARV drug classes nucleoside and nonnucleoside reverse transcriptase inhibitors (NRTI and NNRTI, respectively) and protease inhibitors (PI) have been reported in Brazil, mostly ranging from 5% to 15% . In Northern Brazil, TDR rates ranging from 0% to 21% have been reported; however, studies from this region are still scarce …”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] In Northern Brazil, TDR rates ranging from 0% to 21% have been reported; however, studies from this region are still scarce. 8,[13][14][15][16][17] In the context of a highly endemic region for HIV/AIDS, apparently healthy blood donors recently diagnosed with HIV-1 infection represent important sentinel populations for the assessment of TDR/DRM. As part of the routine screening process of blood donors, it has been assumed that all HIV-1-positive blood donors were honest about not knowing their HIV-positive status and not taking any ARV that could otherwise readily select for DRM.…”
mentioning
confidence: 99%